THE FARM RISK MANAGEMENT OF BESUKI NA-OOGST TOBACCO IN TANJUNGREJO VILLAGE, JEMBER REGENCY - Anggi Lian Yustin Pratama; Soetriono Soetriono; Jani Januar (Socio-Economics/Agribusiness Department, 2018)
Tobacco is considered as one of the commercial plantation crops which has high expected farming profit. Jember Regency is one of the areas in East Java Province that is recognized as production center of tobacco. The major variety of tobacco which can be planted in Jember Regency is the Besuki Na-Oogst’s Tobacco. Besuki Na-Oogst’s Tobacco provides high profit when it is compared to the other commodities cultivated in the area of Tanjungrejo Village. The research goals are to analyze: (1) the farmer’s attitude to the risk in farm management, (2) the income of Besuki Na-Oogst Tobacco’s farmers and (3) the factors that influence the income of Besuki Na-Oogst’s Tobacco farmer in Tanjungrejo Village. The sample method used is simple random sampling. The econometric modeling employed is multiple regression analysis. The results show that (1) among the farmers of Besuki Na-Oogst’s Tobacco is neutral to the risk; (2) the income on 2015 was decreased because of the eruption of Raung Mountain. It influenced all farmers in Tanjungrejo Village. The eruption of Raung Mountain caused the decreasing quality of tobacco leaves as well; (3) the factors affected the income of tobacco farmer in Desa Tanjungrejo was selling price, the cost of seed, labor costs, land area, and dummy of risk lover.